2022
DOI: 10.3389/fimmu.2022.895513
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Tissue Compartment-Specific Protein Signatures in Primary and Metastatic Oropharyngeal Squamous Cell Carcinomas

Abstract: Head and neck squamous cell carcinoma (HNSCC) often presents with locoregional or distant disease, despite multimodal therapeutic approaches, which include surgical resection, chemoradiotherapy, and more recently, immunotherapy for metastatic or recurrent HNSCC. Therapies often target the primary and nodal regional HNSCC sites, and their efficacy at controlling occult distant sites remains poor. While our understanding of the tumor microenvironment conducive to effective therapies is increasing, the biology un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(47 reference statements)
1
0
1
Order By: Relevance
“…However, we found higher levels of B7-H3 expression in both the tumor and stromal compartments of responders compared to non-responders. This finding is consistent with our previous published work on oropharyngeal squamous cell carcinoma (OPSCC), in which we demonstrated that B7-H3 expression in the stroma of nodal metastatic samples was associated with improved overall survival (OS) in patients ( 25 ). Here, we show that V-domain immunoglobulin suppressor of T cell activation (VISTA) was enriched in non-responders.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, we found higher levels of B7-H3 expression in both the tumor and stromal compartments of responders compared to non-responders. This finding is consistent with our previous published work on oropharyngeal squamous cell carcinoma (OPSCC), in which we demonstrated that B7-H3 expression in the stroma of nodal metastatic samples was associated with improved overall survival (OS) in patients ( 25 ). Here, we show that V-domain immunoglobulin suppressor of T cell activation (VISTA) was enriched in non-responders.…”
Section: Discussionsupporting
confidence: 93%
“…B7-H3 expression may be linked to immune suppression, which promotes tumor cell growth. Recent studies have found that in a number of solid tumors, including breast, ovarian, brain, and gastric cancer, as well as Merkel cell carcinoma, showed that high expression of B7-H3 increased tumor size, invasion, and proliferation, which were linked to worse prognosis and overall survival (24). However, we found higher levels of B7-H3 expression in both the tumor and stromal compartments of responders compared to non-responders.…”
Section: Discussioncontrasting
confidence: 56%